2001
DOI: 10.1109/20.947059
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures of FeTaN films in the neck region of magnetic recording heads

Abstract: We found that the columns at the neck region of a magnetic recording inductive head slider composed of FeTaN and NiFe are tilted from the surface normal when the pole materials are sputtered at a low substrate bias power. The electron diffraction patterns show that (110) texture has not strongly developed in the FeTaN film. We have not observed noticeable voids throughout the film on the slider, which suggests the absence of microshape anisotropy. This observation is consistent with our previous study of FeTaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The effect of low substrate bias on Co-Zr-O films sputtered on small-angle substrates can be understood on the basis that low substrate bias effectively helps overcome a slight shadowing effect. The worsening of soft magnetic properties with highpower substrate bias in Co-Zr-O films is not usually seen in other soft magnetic films [12]- [14]. We found that high substrate bias leads to larger size and stronger hcp (002) texture of cobalt particles, and even more severe columnar structure.…”
Section: A Effect Of Substrate Biasmentioning
confidence: 48%
See 2 more Smart Citations
“…The effect of low substrate bias on Co-Zr-O films sputtered on small-angle substrates can be understood on the basis that low substrate bias effectively helps overcome a slight shadowing effect. The worsening of soft magnetic properties with highpower substrate bias in Co-Zr-O films is not usually seen in other soft magnetic films [12]- [14]. We found that high substrate bias leads to larger size and stronger hcp (002) texture of cobalt particles, and even more severe columnar structure.…”
Section: A Effect Of Substrate Biasmentioning
confidence: 48%
“…Substrate bias has been reported to play a different role in FeTaN films. Changing film stress and the orientation of Fe grains contributed to suppression of the perpendicular anisotropy existing in FeTaN films on sloping surfaces [13], [14].…”
Section: A Effect Of Substrate Biasmentioning
confidence: 99%
See 1 more Smart Citation